WORKSHOP PEMANFAATAN MEDIA ONLINE PADLET DAN KAHOOT GAME PADA GURU SD 01 ALKHAIRAT DAN SD O4 ALKHAIRAT KOTA TERNATE - Abdullah, In Hi; Suharna, Hery; Suratno, Joko; Hamid, Hasan (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2024)
Community Service (PKM) was carried out for teachers at SD 01 and 04 Alkhairat, Ternate City. The aim of this PKM is to improve the ability of elementary school teachers to use applications in classroom learning. This PKM is based on the results of discussions held on July 20 2024. The results of the agreement to implement the PKM are: (1) Conducting socialization about applications in learning; (2) Practicing the Online Padlet and Kahoot Game applications in workshops as a simulation; (3) Conduct evaluations in the use of applications in learning. The agreed solution is based on the results of problem identification, namely: (1) In general, students like application-based learning, especially online; (2) Teachers experience difficulties when learning is application-based, both online and offline; (3) lack of knowledge in using learning media; and (4) teachers also have difficulty operating using applications, especially online ones. The solution to this problem needs to be done and is a mutual agreement. A series of services that can be carried out in order to improve the ability to use Online Padlet and Kahoot Games at SD 01 and SD 04 Alhairat, Ternate City. This PKM involves all partners, namely SD 01 and SD 04 Alkhairat, Ternate City. Furthermore, the expected outputs in this PKM are: (1) Conducting socialization about applications in learning; (2) Application Usage Workshop and (3) Third program: FGD to increase knowledge of Online Padlet and Kahoot Game teachers. This activity involved all 26 teachers at SD 01 and SD 04 Alkhairat, Ternate City. Based on the evaluation results, the response was